Genome Sequencing of Mesonia algae K4-1 Reveals Its Adaptation to the Arctic Ocean - Huan, Ran; Huang, JiaFeng; Liu, Dan; Wang, Meng; Liu, CongLing; Zhang, YunQian; Yi, CuiPing; Xiao, Dong; He, HaiLun (Frontiers in Microbiology, 2019)
The special ecological environment of the Arctic has brought about a large number of salt-tolerant and psychrotolerant microorganisms. We isolated two culturable bacterial strains of the genus Mesonia; one from the Arctic ocean, Mesonia algae K4-1, and one from the tropical sea, Mesonia sp. HuA40. Our genome analysis and phenotypic experiments indicated that Mesonia algae K4-1 is a moderately halophilic and psychrophilic bacterium. Mesonia algae K4-1 can tolerate 3-14% NaCl and grow at a wide range of temperatures from 4 to 50 °C. Mesonia sp. HuA40 is a mesophilic bacterium that can only grow with 3-9% NaCl. In addition, the salt adaptation strategy of Mesonia algae K4-1 accumulates organic osmolytes in the cell. RNA helicases, glutathione and organic compatible solutes may play important roles in maintaining the metabolism and physiological function of Mesonia algae K4-1 under cold stress. Moreover, the ability of Mesonia algae K4-1 to adapt to an oligotrophic marine environment is likely due to the synthesis of a large number of extracellular polysaccharides and the secretion of various families of extracellular proteases. This study systematically analyzed the relationship between genomic differentiation and environmental factors of the Mesonia genus and revealed the possible adaptation mechanism of Mesonia algae K4-1 in the extreme Arctic marine environment at the genomic level.